2023 Korean Endocrine Society Consensus Guidelines for the Diagnosis and Management of Primary Aldosteronism - Ha, Jeonghoon; Park, Jung Hwan; Kim, Kyoung Jin; Kim, Jung Hee; Jung, Kyong Yeun; Lee, Jeongmin; Choi, Jong Han; Lee, Seung Hun; Hong, Namki; Lim, Jung Soo; Park, Byung Kwan; Kim, Jung-Han; et al. (Endocrinology and Metabolism, 2023)
Primary aldosteronism (PA) is a common, yet underdiagnosed cause of secondary hypertension. It is characterized by an overproduction of aldosterone, leading to hypertension and/or hypokalemia. Despite affecting between 5.9% and 34% of patients with hypertension, PA is frequently missed due to a lack of clinical awareness and systematic screening, which can result in significant cardiovascular complications. To address this, medical societies have developed clinical practice guidelines to improve the management of hypertension and PA. The Korean Endocrine Society, drawing on a wealth of research, has formulated new guidelines for PA. A task force has been established to prepare PA guidelines, which encompass epidemiology, pathophysiology, clinical presentation, diagnosis, treatment, and follow-up care. The Korean clinical guidelines for PA aim to deliver an evidence-based protocol for PA diagnosis, treatment, and patient monitoring. These guidelines are anticipated to ease the burden of this potentially curable condition.